FEATURES OF THE USE OF INNOVATIVE EDUCATIONAL TECHNOLOGIES IN IMPROVING THE MODERN EDUCATION SYSTEM OF UZBEKISTAN (World Bulletin of Social Sciences, 2023)
This article describes the features of innovative educational technologies in improving the modern education system of Uzbekistan, the importance of educational reforms in the development strategy of New Uzbekistan, and factors in the development of modern education. The article also expresses opinions on the adoption by teachers of educational institutions of an innovative approach, the development of innovative skills, the ability to correctly use pedagogical technologies in educational practice.